Sustainable asphalt modification using palm oil fuel ash, garnet waste, and sawdust: performance and correlation analysis - Wan Noor Hin, Mior Sani; Putra Jaya, Ramadhansyah; Khairil Azman, Masri; Haryati, Yaacob; Zaid Hazim, Al-Saffar (Springer, 2025)
Recently, the volume and growth of industrial as well as agricultural waste have caused environmental pollution. However, this issue can be mitigated through recycling and reutilization of such waste products. Therefore, this paper evaluated the potential of palm oil fuel ash (POFA), garnet waste, and sawdust as sustainable modified asphalt binders and mixtures as a substitute strategy to encourage waste recycling in road pavement construction. POFA, garnet waste, and sawdust were blended individually with asphalt grade 60/70 with varied amounts of 0% (control), 3%, 6%, and 9%. Moreover, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray fluorescence (XRF), as well as X-ray diffraction (XRD) were utilized to analyze the microstructures of raw waste materials. The physical characteristics with regard to the modified asphalt binder were determined by employing softening point, penetration, and viscosity tests. Consequently, the modified asphalt mixture was assessed using the Marshall stability test. Specifically, adding 6% POFA, 3% garnet waste, and 3% sawdust performs best in stability as a modified asphalt mixture. The correlation of stability, flow, bulk density, and stiffness for POFA-, garnet waste-, and sawdust-modified asphalt mixture was significant, with a strong coefficient of determination (R2) for all Marshall stability parameters. The statistical analysis, including one-way ANOVA and Tukey’s HSD test, revealed that the percentage levels of 0%, 3%, and 6% exhibited significant differences in stability and stiffness, highlighting the optimal modification levels for enhanced mechanical performance. These findings highlight the potential of POFA, garnet, and sawdust as effective alternative additives as asphalt modifiers, contributing to sustainable road construction by promoting the use of industrial and agricultural waste materials, reducing environmental impact, and enhancing pavement performance.